One Lipid, Two Synaptic Plasticity Pathways - Robinson, Richard (PLOS Biology, 2015)
A new study identifies an unexpected role for lysophosphatidic acid in modulating the strength of both excitatory and inhibitory synapses in the brain, but by different mechanisms. Read the accompanying Research Article.